Constitution of the Lymphatic System - Valeriy M. Petrenko, PhD, ScD (International Journal of Biomedicine, 2012)
The lymphatic system consists of two types segments – general (systemic or periarterial) and special (own, intervalvular). The segments organize all the system’s reactions in response to its environmental influences. This paper presents the results of the research the common structure of all the sections of the lymphatic bed.